A new dead-time determination method for gamma-ray detectors using attenuation law - AKYÜREK, TAYFUN (KOREAN NUCLEAR SOC, 2021)
This study presents a new dead-time measurement method using the gamma attenuation law and generalized dead-time models for nuclear gamma-ray detectors. The dead-time of the Nal(TI) detection system was obtained to validate the new dead-time determination method using very thin lead and polyethylene absorbers. Non-paralyzing dead-time was found to be 8.39 mu s, and paralyzing dead-time was found to be 8.35 mu s using lead absorber for Nal(TI) scintillator detection system. These dead-time values are consistent with the previously reported dead-time values for scintillator detection systems. The gamma build-up factor's contribution to the dead-time was neglected because a very thin material was used. (C) 2021 Korean Nuclear Society, Published by Elsevier Korea LLC.
Keywords: dead-time; non-paralyzing model; paralyzing model; DMRAL method